Integrating Strategic PAUD Management Approaches in Early Childhood Education; A Systematic Literature Review on Foundational Phase Quality Services - Mardiyati, Mardiyati; Nahdiah, Indah; Setiawan, Edwar; Suwandari, Lilis (Journal of Educational Management Research, 2025)
Early Childhood Education (ECE) represents a critical stage in shaping the holistic development of children. Despite its significance, existing studies tend to address ECE management in fragmented dimensions, lacking an integrated managerial framework. This study aims to synthesize diverse managerial approaches into a systemic framework focused on the foundational phase, to support the delivery of high-quality educational services. Employing a Systematic Literature Review (SLR) with an exploratory qualitative design, the research adheres to the PRISMA guidelines. Data were retrieved from scholarly databases including Google Scholar, Garuda, SINTA, and DOAJ, with inclusion criteria comprising open-access articles published between 2015 and 2025 that focus on ECE management. Thematic content analysis identified five key categories: curriculum and instruction, institutional management and leadership, teacher professionalism, holistic-integrative approaches, and strategic innovations. The findings reveal that high-quality ECE management during the foundational phase is underpinned by the integrated implementation of these five dimensions. The study concludes that a systematic and interconnected managerial approach is essential for enhancing ECE quality and provides practical implications for school administrators, policymakers, and educational researchers.